Designing A Conceptual Model of the Contributing Factors in Students’ Academic Burnout - Hashemi, Touraj; Bayrami, Mansour; Vahedi, Shahram; Dastouri, Ramin (International Journal of Psychosocial Rehabilitation, 2020)
The present study was conducted to design a conceptual model of the contributing factors in pupils’ academic burnout. Therefore, a conceptual model of the contributing factors in academic burnout was designed based on the review of literature. A population consisting of 400 subjects in the third grade of the middle school in Tabriz were selected using multistage clustering sampling. The Breso’s academic burnout questionnaire, Walrand’s academic motivation questionnaire, Sherer’s self-efficacy questionnaire, Ferasat’s perfectionism questionnaire, Connor-Davidson Resilience scale, and Miller and Brown’s self-regulation were used to data collection. Data analysis through the structural equations modeling method showed that the conceptual model fit desirably and the fitness indices including GFI, AGFI, CFI, IFI and RMSEA were at a desirable level. According to the findings of the present study, it can be inferred that the academic motivation, self-efficacy, perfectionism (adaptive and maladaptive), resilience and self-regulation are the factors predicting the academic burnout where the academic motivation and self-efficacy mediate the relationships between the independent variables and academic burnout. Hence, it can be stated that the academic burnout is influenced by the motivational factors, personal characteristics and life skills where the motivational factors can change the impacts of personal characteristic and skill variables on academic burnout.